Policy challenges affecting the electric vehicle manufacturing sector in South Africa - Mateko, Freeman Munisi (University of the Witwatersrand, Johannesburg, 2024)
The evolution of technology has brought many changes to the automotive sector on a global scale. Different economies in the Global South and Global North are making strides to adopt modern technology, such as electric vehicles, which are more efficient than internal combustion engine vehicles. Electric vehicles have zero emission levels and this is crucial for supporting climate change action. Economies that have adopted electric vehicles succeeded due to robust policies and financial incentives for car manufacturers, among other factors. The aim of this research was to explore the extent to which the policy environment facilitates for increased adoption and manufacturing of electric vehicles (EVs) in South Africa. This research is in line with various Sustainable Development Goals (SDGs). It supports SDG 7 by encouraging the use of electric vehicles for cleaner energy, as well as SDG 9 by advocating for automotive sector innovation and infrastructural development. Furthermore, the emphasis on lowering emissions coincides with SDGs 11 and 13 by promoting sustainable urban environments and climate action. In terms of the research methodology, the study was based on qualitative research techniques. Interviews and literature review were used for data collection. Six policy documents were analyzed in this study. The target population for the study were the stakeholders in the South African car manufacturing sector. Purposive sampling was used to select a total of ten participants for the study. Data was analyzed through content and thematic analysis techniques. The results of primary study demonstrated how ambiguous South Africa's current electric vehicle policy environment is. Additionally, it was determined that some factors must be considered to guarantee a seamless switch to electromobility. Developing and executing electric vehicle policies, maintaining a steady supply of energy, lowering import taxes on EV parts, skill development, providing purchase subsidies, and providing production and technological incentives are a few of these elements. In terms of policy recommendations, it was suggested that there is need for timeous implementation of electric vehicles policy, producing battery electric vehicles, promoting research and development on electric vehicles and there is need for increased government support towards car manufacturers in South Africa.
A research report submitted in fulfillment of the requirements for the Master of Management, In the Faculty of Faculty of Commerce, Law and Management, Wits School of Governance, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; 1.1 automotive sector; climate; electric vehicles; innovation; South Africa; Sustainable Development Goals; SDG-12: Responsible consumption and production; SDG-9: Industry, innovation and infrastructure